PENERAPAN POLA HIDUP SEHAT DALAM PENDIDIKAN JASMANI UNTUK MENINGKATKAN KARAKTER DISIPLIN PADA SISWA MAS KHULAFAUR RASYIDIN - Imam Wahyudi; Victor Simanjuntak; Muhammad Fachrurrozi Bafadal; Rio Wardhani (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
A clean and healthy lifestyle is a health behavior that is carried out out of a person's concern for himself, family members, and other people in the surrounding environment. The application of a healthy lifestyle is not only washing hands with soap but also disposing of garbage in its place in the community environment. The aim is to find out whether students carry out clean and healthy living behaviors as the formation of their disciplinary character. This research method uses a type of classroom action research. The results obtained in implementing a healthy lifestyle through physical education can improve the character of discipline in MAS Khulafaur Rasyidin students, namely there is an increase in student discipline, namely in the implementation of the pre-cycle there are 23.3% of students experiencing good discipline while in cycle I there is a value of 50% increase the results obtained amounted to 26.7% of students who experienced changes when implementing a clean and healthy lifestyle. In addition, it was continued with cycle II with a fairly high value of 93.33% with an increase of 43.33%. The conclusion of this study is that the application of a healthy lifestyle in physical education learning shows an increase in the discipline of Khulafaur Rasyidin MA students. This increase can be seen from an increase in student participation which includes student activity, student discipline, and student interest in adopting healthy living habits.